Effect of diazotated sulphonated polystyrene films on the calcium oxalate crystallization - Vásquez-Quitral, Patricio (2017)
Pathological crystallization of calcium oxalate (CaOx) inside the urinary tract is called calculi or kidney stone (Urolithiasis). CaOx exhibits three crystalline types in nature: CaOx monohydrate COM, dihydrate COD and trihydrate COT. COD and COM are often found in urinary calculi, particularly COM. Langmuir monolayers, membrane vesicles, phospholipids’ micelles, among others, have been adopted as simplified biomimetic template-models to study in vitro the urolithiasis through CaOx. The nucleation and crystal growth of COM on self-assembled lipid monolayers have revealed that the negatively charged phosphatidylserine interface is a strong promoter of COM. Herein, we describe the synthesis and physicochemical characterization of diazotated sulphonated polystyrene films (DSPFs), prepared from various aminocompounds varying their polarity degree i.e., polar, non-polar and acidic DSPF derivatives. We also used these DSPFs as polymeric templates in crystallization experiments of CaOx in vitro. Images obtained by optical microscopy and scanning electron microscopy confirmed the precipitation of COM crystals on the DSPF surface. The employment of functionalized polymeric films as templates for CaOx crystallization represents a viable approach for understanding inorganic mineralization.